Optimization of Deep Eutectic Solvent Extraction of Phenolic Acids and Tannins from Alchemilla vulgaris L. - Martina Jakovljević Kovač; Stela Jokić; Igor Jerković; Maja Molnar (Plants, 2022)
Alchemilla vulgaris L. is a good source of antioxidant components with an emphasis on phenolic acids and tannins. In this study, gallic acid, ellagic acid, and hydrolyzable tannins (HT) were extracted from this plant with different deep eutectic solvents (DESs), varying the amount of added H2O, temperature and extraction time. Seventeen DESs (n = 3) were used for the extraction, of which choline chloride:urea (1:2) proved to be the most suitable. The selection of the best solvent was followed by the examination of the influence of the extraction type and parameters using response surface methodology (RSM). Gallic acid content was in the range of 0.00–1.89 µg mg−1, ellagic acid content was 0.00–12.76 µg mg−1 and hydrolyzable tannin (HT) content was 3.06–181.26 µgTAE mg−1, depending on the used technique and the extraction conditions. According to the results, extraction by stirring and heating was the most suitable since the highest amounts of gallic acid, ellagic acid, and HT were extracted, and the obtained optimal values using response surface methodology (RSM) are confirmed by experimentally obtained values.